Numerical Investigation Of The Impact On The Flow Patterns In The Spillway Crest Elevation Hydraulic Jump Along The Side Weirs In Open Channel - Negar Bagheri; Mohammad Saeed Toranji; Afshin Eghbal zade (مهندسی و مدیریت ساخت, 2016)
Side overflows are one of the most important hydraulic structures in water control and control systems. The outlet flow is a three-dimensional overflow that causes these overflows to have a complex hydraulic. Under certain conditions, the presence of a lateral overflow causes a jump in the main channel, which is considered less significant, the numerical validation of the 3D-FLOW of the researchers. In this paper, after 3D modeling of hydraulic jump in lateral overflows, using laboratory data software, the effect of overhead crown height on hydraulic jump characteristics was investigated. The results showed that with the decrease of the height of the overflow crown, the amount of landing number increases in the initial jump, which leads to a stronger hydraulic jump. Also, with decreasing the height of the overflow crown, the level of water level fluctuations and hydraulic jump height increase.